2023
DOI: 10.1136/openhrt-2022-002155
|View full text |Cite
|
Sign up to set email alerts
|

Young athlete’s growing heart: sex differences in cardiac adaptation to exercise training during adolescence

Abstract: BackgroundAthlete’s heart is a condition of exercise-induced cardiac remodelling. Adult male endurance athletes more often remodel beyond reference values. The impact of sex on remodelling through adolescence remains unclear. Paediatric reference values do not account for patient sex or exercise history. We aimed to study the effect of sex on cardiac remodelling throughout adolescence.MethodsWe recruited 76 male (M) and female (F) 12-year-old cross-country skiers in a longitudinal cohort study. Echocardiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…It has been well established that high aerobic exercise capacity is physiologically characterized by higher function of, among others, cardiac contractile parameters both in the cell and the whole organ 30 . − 32 Although debate continues as to how much of this is inherited or acquired (nature versus nurture), human 33,34 and experimental 26,35,36 genetic association studies and the current LCR–HCR model system 7 10,26,29 have convincingly shown that a robust inherited component prevails that also at least partly explains the phenotype segregation between those that score for low and those that score for high exercise capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well established that high aerobic exercise capacity is physiologically characterized by higher function of, among others, cardiac contractile parameters both in the cell and the whole organ 30 . − 32 Although debate continues as to how much of this is inherited or acquired (nature versus nurture), human 33,34 and experimental 26,35,36 genetic association studies and the current LCR–HCR model system 7 10,26,29 have convincingly shown that a robust inherited component prevails that also at least partly explains the phenotype segregation between those that score for low and those that score for high exercise capacity.…”
Section: Discussionmentioning
confidence: 99%
“…This has also been advocated for by clinical trials evidencing both longterm benefit and safety of introducing added levels of physical activity to children. 30,38 As indicated above, a mechanism that explains the blunted car- widening divergence remains unknown, but it appears to be genetic in origin. [7][8][9]28 Identifying this genetic mechanism would be desirable.…”
Section: Mechanisms and Implications Of Divergencementioning
confidence: 98%
“…This is especially important in patients with previous cardiac surgery as they often have more pulmonary abnormalities on spirometry than those without surgery. Musculoskeletal training has been shown to increase skeletal muscle mass, including cardiac mass which can improve cardiac stroke volume ( 36 ). Other cardiac changes to optimize function can include addressing residual cardiac lesions, medication compliance, and regular surveillance in addition to fitness training.…”
Section: Discussionmentioning
confidence: 99%
“…In general, dilation of the chambers accompanied by increased myocardial mass is observed, and low-normal resting functional measures are also frequent findings in adult athletes [1,2]. Pediatric athletes represent a unique population in which the interpretation of Right Ventricular Structure and Function in Adolescent Athletes: A 3D Echocardiographic Study different investigations is a clinical issue; yet there is a lack of data and evidence [3,4].…”
Section: Introductionmentioning
confidence: 99%